SUSTAINABILITY LEVEL LEMURU (SARDINELLA LEMURU) MANAGEMENT ECONOMIC AND SOCIAL DIMENSION IN THE BALI STRAIT'S WATERS - Tanjov, Yulia Estmirar; Satyawan, Noar Muda; Bramana, Aditya; Jaya, Made Mahendra; Khikmawati, Liya Tri; Sarasati, Wulandari; Mainnah, Muth; Azis, Muh. Arkam; Purwanto, Agus (Departemen PSP IPB, 2025)
This study aims to evaluate the persistence of lemuru management in the waters of the Bali Strait from social and economic perspectives. The methodology involves observations and interviews. Data utilized are based on direct observations and interviews with fishermen in the Pengambengan village. Fishermen interviewed were randomly selected and considered to represent the total lemuru catch using purse seines. Data were analyzed using Monte Carlo analysis with the RAPFISH method to determine which behaviors impact each social and economic factor. RAPFISH ordination results in the economic domain showed an index of 48,36, while in the social dimension, it had an index value of 44,48. These index results indicate that lemuru fisheries management for both economic and social dimensions is deemed less sustainable. Key words: lemuru, fisheries management, PPN Pengambengan